Effect of ZrO2 addition on microstructure, morphology and pressure sensing behavior of Pb(ZrxTi1-x)O3 ceramics sintered in AI2O3 environment - Norhashimah Ramli,; Muhamad Mat Salleh,; Muhammad Yahaya,; Mohammad Hafizuddin , (Universiti Kebangsaan Malaysia, 2009)
The effect of ZrO2 addition on the microstructure, morphology and pressure sensing behaviour of Pb(ZrxTi1-x)O3 ceramics was studied in five different compositions of ZrO2, namely x = 0.48, 0.50, 0.52, 0.54 and 0.56. The samples were prepared through the solid-state reaction method using high purity metal oxides powders. In order to control the PbO losses due to high temperature sintering, a novel approach were explored whereby the samples were sintered in Al2O3 environment. Structural investigation using X-ray diffraction (XRD) method revealed that all samples exhibited a tetragonal crystal structure. However the c/a lattice parameters ratios exhibited a decreasing trend as the ZrO2 content was increased, indicating that PZT crystals gradually evolved towards pseudocubic structure. SEM micrographs showed different morphology of each composition with the grain size varies in the range of 1.5 μm to 3.15 μm. The performance of pressure sensing behaviour showed that sample with composition x = 0.52 exhibited the best piezoelectric properties with high sensitivity. However, all samples failed to show good stability and repeatability due to slow recovery after severe lattice strain.